Electrochemical polarization analysis for optimization of external operation parameters in zinc fuel cells. Issue 48 (4th August 2020) - Sangeetha, Thangavel; Yan, Wei-Mon; Chen, Po-Tuan; Yang, Cheng-Jung; Huang, K. David
Abstract : Zinc–air flow fuel cells utilizing zinc particles as fuel possess the potential to evolve as efficient distributed grid generators. Abstract : Zinc–air flow fuel cells utilizing zinc particles as fuel possess the potential to evolve as efficient distributed grid generators. In this research study, electrochemical impedance analysis was employed to determine the optimum design and operational parameters for the feasible maneuver and enhanced energy generation from zinc fuel cells. Polarization resistance ( R p ), ohmic resistance ( R s ), and mass transfer resistance ( R m ) were used as the indicators for determination of the optimum parameters of fuel cell performance. Experimental conditions optimized from previous studies like potassium hydroxide electrolyte with temperature of 25 °C and concentration of 40 wt% zinc powder quantity of 20 g, electrode reaction surface area of 48 cm 2 were followed in the fuel cells used in the present study. Parameters like collector plate material, air flow velocity and cell operating temperature were augmented and finally were all implemented in the fuel cell and operated. Plain nickel or nickel-plated copper were both advantageous as collector plate materials whereas an air flow velocity ranging from 1–3 m s −1 and a cell operating temperature of 25 °C to 45 °C were beneficial for the stability and performance of the zinc fuel cells. Finally, based on the optimized parameters obtained from the above experiments, performance tests of zinc fuel cells were investigated. The maximum power produced was 16.5 W, along with a corresponding voltage of 0.8 V, maximum current density of 430 mA cm −2 and peak power density of 364.6 mW cm −2 . Thus it can be concluded that the fuel cells designed and operated in this study were capable for feasible and efficient future applications.